Determining drivers of financial management behavior among working adults in Malaysia / Azlin Shafinaz Arshad ...[et al.] - Arshad, Azlin Shafinaz; Arshad, Afiza Azura; Mohd Zin, Zahariah; Lubis, Arief Wibisono; Mohamed Haniffa, Putri Hana Najla (Advances in Business Research International Journal, 2021)
Financial management behavior encompasses of four main fields such as saving, expenditure, borrowing and investment. The purpose of this paper is to determine the driver that influences financial management behavior among Malaysian working adults. A survey questionnaire was distributed to 300 Malaysian working adults in three sectors which are the government sector, private sector and self-employed using convenience sampling. A total of 273 responses were collected and deemed usable. Data were analyzed using Statistical Package of Social Sciences (SPSS) 25, looking into the descriptive analysis, reliability analysis and inferential analysis. The findings of the study found that financial knowledge and financial attitude have a significant and positive relationship to financial management behaviour among Malaysian working adults while the locus of control has a negative relationship with financial management behavior among Malaysian working adults. Recommendations are put forth at the end of the study.